The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1159/000169591
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Anemia in Patients on Chronic Dialysis Treated by Hemodiafiltration

Abstract: A group of patients with severe anemia on standard hemodialysis were transferred to polyacrylnitrile hemodiafiltration (HDF), which was arranged in order to obtain an ultrafiltration rate (UF) higher than 100 ml/min. During HDF, despite a significant reduction of the dialysis time, all patients had a significant decrease of predialytic BUN and serum creatinine, and a significant improvement of anemia. Furthermore, a close direct correlation was detected between the percent increase of hemoglobin and the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Plasma β 2 M levels are further reduced in on‐line hemodiafiltration versus high‐flux HD (120,127,134). Uncontrolled studies reported significant improvement in hemoglobin level and a reduced need for erythropoietin in patients using on‐line hemodiafiltration (135–137), possibly as a result of the increased removal of middle molecular inhibitors of erythropoiesis (138).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Plasma β 2 M levels are further reduced in on‐line hemodiafiltration versus high‐flux HD (120,127,134). Uncontrolled studies reported significant improvement in hemoglobin level and a reduced need for erythropoietin in patients using on‐line hemodiafiltration (135–137), possibly as a result of the increased removal of middle molecular inhibitors of erythropoiesis (138).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Towards the end of the 1980s, Gonella et al [1] demonstrated a significant improvement in anemia during HDF compared to bicarbonate hemodialysis (BHD), correlated with improved clearance efficiency as a result of higher convective flows, irrespective of the duration of dialysis session. Subsequently, numerous literature reports have confirmed the erythropoiesis-stimulating effects produced through the use of methods implying a large convective component [2,3,4,5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As compared with conventional hemodialysis (HD), it is associated with a lower morbidity [4], an improvement of uremic neuropathy, and a lower incidence of carpal tunnel syndrome and joint pain [5][6][7]. To what extent the mode of dialysis influences anemia is yet controversial [1,[8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term effects of high-volume OL HDF on uremia and dialysis-related pathology have not been extensively studied, and there are only a few data concerning anemia [1,3,[8][9][10][11][12][13][14][15][16]. The aim of our study was to quantify the influence of high-volume OL HDF on anemia and the related cost savings of recombinant human erythropoietin (rHuEPO) treatment.…”
Section: Introductionmentioning
confidence: 99%